2007
DOI: 10.1002/anie.200604540
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation‐Induced Self‐Assembly of Nanoparticles from a Sphere‐on‐Flat Geometry

Abstract: Self-assembly of nanoscale materials to form ordered structures promises new opportunities for developing miniaturized electronic, optoelectronic, and magnetic devices. [1][2][3][4] In this regard, several elegant methods based on self-assembly have emerged, [5][6][7][8] for example, self-directed self-assembly, [5] and electrostatic self-assembly.[8] Self-assembly of nanoparticles by irreversible solvent evaporation has been recognized as an extremely simple route to intriguing structures. [9][10][11][12] How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
226
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 230 publications
(234 citation statements)
references
References 33 publications
8
226
0
Order By: Relevance
“…The model incorporates wettability, capillarity, evaporation, convective transport of the solution and diffusion of the solute and has been derived employing a long-wave approximation. We find that a strong nonlinear dependence of viscosity (i.e., the front mobility) on concentration triggers, in an intricate interaction with evaporation and diffusion, the deposition of periodic and aperiodic line patterns as observed in experiments for many different materials and settings [2,[5][6][7][8][9][10][11]30]. We believe that the model explains a basic mechanism for the formation of regular line patterns.…”
supporting
confidence: 51%
“…The model incorporates wettability, capillarity, evaporation, convective transport of the solution and diffusion of the solute and has been derived employing a long-wave approximation. We find that a strong nonlinear dependence of viscosity (i.e., the front mobility) on concentration triggers, in an intricate interaction with evaporation and diffusion, the deposition of periodic and aperiodic line patterns as observed in experiments for many different materials and settings [2,[5][6][7][8][9][10][11]30]. We believe that the model explains a basic mechanism for the formation of regular line patterns.…”
supporting
confidence: 51%
“…This changes when the experiments are performed in a controlled way on smaller scales: Recently, both polymer solutions [21][22][23] and (nano)particle suspensions [24][25][26] have been employed in various small-scale geometries where one is able to exercise greater control over the contact line as it recedes due to evaporation. As a result, strikingly regular line patterns are created, where the deposited structures show typical distances ranging from 10-100µm.…”
Section: Introductionmentioning
confidence: 99%
“…8 In our previous work, we reported that concentric rings of electrically conducting polymer and organometallic polymer of high regularity were formed naturally and spontaneously via controlled, repetitive "stick-slip" motion of the three-phase contact line when a drop of polymer solution was confined either between two crossed cylindrical mounts covered with single crystals of mica sheets 10 or between a spherical lens made of silica and a Si substrate (sphere-on-flat geometry), resulting in a capillary-held polymer solution (i.e., capillary bridge). [11][12][13][14][15][16][17] The evaporation in this geometry was restricted to the edge of the droplet, and the "stick-slip" cycles resulted in hundreds of concentric rings with regular spacing, very much resembling a miniature archery target. Each ring was nanometers high and several microns wide.…”
Section: Introductionmentioning
confidence: 99%